2018
DOI: 10.1097/j.pain.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study investigating frequency and features of definitely diagnosed diabetic painful polyneuropathy

Abstract: This cross-sectional multicentre study aimed at investigating frequency and features of painful diabetic polyneuropathy. We consecutively enrolled 816 patients attending hospital diabetic outpatient clinics. We first definitely diagnosed diabetic polyneuropathy and pure small-fibre polyneuropathy using clinical examination, nerve conduction study, and skin biopsy or quantitative sensory testing. Adhering to widely agreed criteria, we then identified neuropathic pain and diagnosed painful polyneuropathy using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 44 publications
2
49
3
Order By: Relevance
“…This has been stressed in several previous reviews. However, the detection of DN is challenging in clinical practice due to the lack of a clear consensus for the definition and optimal clinical assessments to diagnose DN. Similar differences have been encountered for pain, where the criteria for neuropathic pain have also varied considerably.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…This has been stressed in several previous reviews. However, the detection of DN is challenging in clinical practice due to the lack of a clear consensus for the definition and optimal clinical assessments to diagnose DN. Similar differences have been encountered for pain, where the criteria for neuropathic pain have also varied considerably.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, they found pain being correlated with more severe DPN. In contrast, the Italian multicenter study of 816 type 1 and type 2 diabetes patients found female sex to be a risk factor for PDPN using the same definition of PDPN and DPN as the PiNS study. They showed that patients with type 2 diabetes had a higher risk of neuropathy compared with patients with type 1 diabetes.…”
Section: Differences and Similarities Between Pdpn And Dpnmentioning
confidence: 92%
See 3 more Smart Citations